The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s1516-44462002000200006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prescription and dispensation of psychotropic medications in two cities in the State of São Paulo, Brazil

Abstract: OBJECTIVES: To investigate the prescription and dispensation of psychotropic medications through the analysis of the prescriptions/notices kept at various institutions in two cities in the state of São Paulo. METHODS: The prescriptions kept at drugstores, magistral pharmacies, primary care settings and hospitals were collected and analyzed in collaboration with the Sanitary Vigilance agencies in the year of 1999. The information in the prescriptions/notices were typed and tabulated. RESULTS: A total of 108,215… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
21

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 10 publications
3
26
0
21
Order By: Relevance
“…A total of 108,215 prescriptions were processed and 76,954 were of benzodiazepine drugs. Another relevant fact is the destination of these prescriptions: women received more prescriptions than men (12) . Another study addressing the use of psychotropic drugs and carried out in a Family Health unit in the northern region of Natal found that 50 out of 59 participants used psychotropic drugs, of which 31 were women and 19 were men.…”
Section: Medical Consultation and Transcription Of Prescriptionsmentioning
confidence: 99%
“…A total of 108,215 prescriptions were processed and 76,954 were of benzodiazepine drugs. Another relevant fact is the destination of these prescriptions: women received more prescriptions than men (12) . Another study addressing the use of psychotropic drugs and carried out in a Family Health unit in the northern region of Natal found that 50 out of 59 participants used psychotropic drugs, of which 31 were women and 19 were men.…”
Section: Medical Consultation and Transcription Of Prescriptionsmentioning
confidence: 99%
“…[12][13][14][15] Populationbased studies on the consumption of these medications have been accomplished on younger individuals, 16,17 and the benzodiazepine consumption was investigated in a much wider context, which was the use of psychopharmacs. [18][19][20] The population-based studies showed benzodiazepines as the most commonly used psychopharmacs in the adult population, [17][18][19][20] and among these, Diazepam was the most used chemical substance. 16,18,19 In these studies, the consumption of benzodiazepines was higher among women, 16,17 among older subjects and among the wealthy.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] The population-based studies showed benzodiazepines as the most commonly used psychopharmacs in the adult population, [17][18][19][20] and among these, Diazepam was the most used chemical substance. 16,18,19 In these studies, the consumption of benzodiazepines was higher among women, 16,17 among older subjects and among the wealthy. 17 To our knowledge, there are no Brazilian studies on the profile of use of benzodiazepines among community-dwelling older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Eis algumas delas: sistema gerencial e de garantia de qualidade 42 ; nomenclatura do medicamento 43 ; caligrafia médica 44 ; distração momentânea; estresse profissional 45 ; sistemas de prescrição, transcrição, dispensação e administração de medicamentos; falta de conhecimento ou treinamento inadequado 46 ; fontes inadequadas de informação sobre medicamentos 47 ; erros humanos 5 .…”
Section: Estratégiasunclassified